International Refugee Law III: The Principle of Non-Refoulement - Kevlishvili , Mariam; Zaalishvili, Tamta (International Criminal Law, Humanitarian Law and Refugee Law From The Perspective of Human Rights Law, 2026)
The principle of non-refoulement is a fundamental aspect of international law that prohibits states from returning individuals to territories where they face persecution, torture, or serious harm. This principle is enshrined in the 1951 Refugee Convention and reinforced by human rights law, customary international law, and humanitarian law. It applies to refugees and asylum seekers, ensuring their protection from being returned to dangerous situations. While generally considered absolute, limited exceptions exist for national security or serious crimes. Despite its importance, challenges persist in its application and enforcement, including restrictive interpretations and variability among states.This Chapter provides a comprehensive review of the principle of non-refoulement, covering its development, interpretation, and application in various international and national contexts. The review is structured around four main sub-chapters, each focusing on a different aspect of the principle.The first sub-chapter explores the principle of non-refoulement under the Refugee Convention, including its historical development, interpretation, and exceptions. The second sub-chapter examines the principle’s application in the case law of UN bodies, including the UNHCR and judicial/quasi-judicial bodies. The third sub-chapter discusses the principle’s scope and application under the European Convention on Human Rights and the practice of the European Court of Human Rights. The final sub-chapter reviews the principle’s application in other regional international courts, such as the Court of Justice of the European Union and the Inter-American Court of Human Rights, as well as national courts.Overall, this Chapter provides a thorough analysis of the principle of non-refoulement, highlighting its importance in protecting individuals from persecution, torture, and serious harm. It also underscores the challenges and complexities that arise in its application and enforcement, including restrictive interpretations and variability among states.Keywords: non-refoulement, refugee, persecution, international protection, asylum